‘A most peculiar form of disease’: The creation of anorexia nervosa in late nineteenth-century Britain - Sookdeosingh, RV (2019)
Anorexia nervosa appeared as a newly named disorder in the 1870s in Britain, leading historians and other scholars to pinpoint this as the origin point of a medicalised understanding of female food refusal. An abiding interest in locating the historical roots of this contemporary disorder has led scholars to emphasise the ways in which anorexia nervosa is therefore an historical and not merely a ‘modern’ disorder. It has also resulted in a body of scholarship that emphasises continuity over discontinuity in anorexia nervosa’s medicalised history. This has meant that scholars have neglected to ask why after its introduction into the medical lexicon, anorexia nervosa failed to become established as a credible, universally recognised and endorsed, and utile diagnostic category.